Introduction of the Comet assay for the evaluation of oxidative stress, antioxidant effects and environmental pollutants effects on animal cells - Romana MARINŠEK-LOGAR (Acta Agriculturae Slovenica, 1999)
DNA damage within single mammalian cells can be one of the earliest signs of a whole range of health problems, including disease, diet and exposure to occupational or environmental toxins. The Comet assay is a relatively simple and inexpensive method for measuring this damage. It works by determining the number of breaks in the strands of DNA within the cell. Cells are embedded in agarose gel on a microscopic slide and washed to remove the cell membranes, soluble cell contents and histones from the nucleus. An electric field is then activated across and the loops of damaged DNA are pulled towards the anode. Epifluorescence microscopy of stained gels shows the image which gives the techique its name: a clump of undamaged DNA (the head) with the loops pulled away, forming a tail of a comet. We report herein the checking of the Comet assay for the evaluation of oxidative stress on chicken, mouse and pig blood cells, pig sperm cells and chicken hepatocytes. We intend to use the Comet assay as a quantitative method in some nutritional experiments with domestic animals including oxidative food components and antioxidants and for the evaluation of some environmental pollutants effects on animal and human cells.